Trade balance effects on economic growth: Evidence from European Union countries - Deimante Blavasciunaite; Lina Garsviene; Kristina Matuzeviciute (Economies, 2020)
A growing number of recent research analyse the trade balance impact on economic growth. However, ambiguous results of studies imply the need for the research as the deteriorating trade balance hinders economic growth. This research aims to investigate the impact of the trade balance on economic growth as well as to evaluate it during the periods of trade deficit. Our estimations are based on the European Union (EU) 28 countries panel data over the period of 1998-2018, using the OLS method of multivariate regression analysis with fixed effects and focusing on two strategies: (i) including all trade balance periods, and (ii) adding deficit dummy variable seeking to evaluate whether during deficit periods we can find different and significant effect on economic growth. Evaluating all trade balance periods, the obtained results indicate the negative and lagging impact of the trade balance on economic growth, and no significant differences of the impact were identified during the deficit periods. The deterioration of trade balance reduces average economic growth and from linear relationship evaluation, we can state that it does not matter whether it starts from trade deficit or surplus result. The results obtained may also obscure the possibility of a non-linear effect, which would suggest a stronger negative impact on economic growth when the trade balance deteriorates in the presence of a large trade deficit. When discussing directions for further research it would make sense to consider other factors, such as the size of the deficit and its permanence.
Keywords: C23; F40; F43; 330; economic growth; trade balance; panel estimates